Analisis Kebijakan Keamanan Siber di Indonesia: Studi Kasus Kebocoran Data Nasional pada Tahun 2024 - Imanuel Toding Bua; Nur Isdah Idris (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The 2024 data breach incident at Indonesia's National Data Center (PDN) marked a major crisis in the governance of national cybersecurity. This study examines the causes, threats, proposed solutions, and the roles of both the government and the public in responding to such breaches. The research employs a literature review and media framing analysis, focusing on news coverage and government policy responses. Findings indicate that systemic vulnerabilities, inadequate infrastructure readiness, and human factors are the primary causes of the breach. The resulting threats include economic and social losses, a decline in public trust, and the risk of data misuse. Proposed solutions involve strengthening regulations, enhancing technical capacity, and increasing public awareness through education. The active participation of civil society and swift government response are critical to restoring trust and preventing similar incidents in the future.